Upaya Meningkatkan Kompetensi Writing Descriptive Text Melalui Team Pair Solo Based on My Idol Kelas VII A SMP Negeri 3 Ambarawa Semester 2 Tahun Pelajaran 2014/2015 - Susilowati, Sri (Jurnal Profesi Keguruan, 2016)
The purpose of this study was to describe the changes in the mindsets of students and improving the competence to write a descriptive passage Team Pair Solo models. E class VII SMP Negeri 3 Ambarawa totally was 33 people consisting of 18 male and 15 female students. The data collection is done by using the method of observation and performance. This is evident from the observation of changes in attitude / behavior of learners at 0% on the initial conditions, being 6.07% in the first cycle and increased again to 36.4% in the second cycle. Increasing of changing in attitudes / behaviors learners' learning affects the learning outcome. The average grade of 64.7% with the thoroughness 7 learners in the initial conditions increased to 72.2% with the thoroughness of a total of 14 students in the first cycle and increased again to 78.2% by the thoroughness of as many as 28 students in the second cycle. Team Pair Solo learning model can be used as an alternative in the effort to improve the learning active role and learning outcomes.